Relationships between dipstick proteinuria and risk of hearing impairment among Japanese workers: a prospective cohort study - Mitsumasa Umesawa; Toshimi Sairenchi; Yasuo Haruyama; Gen Kobashi; Mikako Hara (BMJ Open)
Objectives Hearing impairment is among the most significant health problems, and the number of adults with hearing impairment is increasing worldwide. Therefore, the prevention of hearing impairment is important. Proteinuria appears to be a risk factor for hearing impairment, but no prospective studies have examined the association between proteinuria and hearing impairment risk. This prospective study aimed to clarify the association between dipstick proteinuria and risk of hearing impairment.Design This was a prospective cohort study based on annual health check-up data, 2008–2016.Setting Data were collected on 7005 employees of a single company who worked in offices and factories throughout Japan.Participants We analysed data from 5699 subjects (88.6% men) who underwent annual health check-ups twice or more from 2008 to 2016, had no missing data, and were free from hearing impairment at baseline. We regarded the first health check-up as the baseline examination.Primary and secondary outcome measures Hearing tests were performed using audiometry at two frequencies (1 and 4 kHz) during the health check-ups. Defining total moderate hearing impairment as the inability to respond to 30 dB at 1 kHz and/or 40 dB at 4 kHz, we examined the association between dipstick proteinuria at baseline and risk of hearing impairment at final examination.Results Total moderate hearing impairment was noted in 162 (2.8%) subjects. Compared with subjects without proteinuria at baseline, the multivariable adjusted OR (95% CI) was 5.35 (1.87–15.25) for subjects with proteinuria ≥2+, 0.92 (0.40–2.13) for those with proteinuria +/−, and 1.33 (0.63–2.80) for those with proteinuria+ at baseline.Conclusions Severe dipstick proteinuria was positively associated with risk of hearing impairment in the future. Our results suggest that medical examinations including urine testing are effective for detecting subjects with high risk of hearing impairment.